Midwives Performance in Early Detection of Growth and Development Irregularities of Children Based on Task Commitment - Sri Utami; Nursalam Nursalam; Rachmat Hargono; Rekawati Susilaningrum (Institute of Advanced Engineering and Science, 2016)
The purpose of this study was to analyze the performance of midwives based on the task commitment. This was an observational analytic with cross sectional approach. Multistage random sampling was used to determine the public health center, proportional random sampling to selected participants. The samples were 222 midwives in the public health center of Surabaya City. Data were collected by questionnaires on exogenous variables and sheet of data collectors for the performance of midwives. Data was analyzed by using Partial Least Square (PLS). This study found the results of the self leadership directly affects the performance with the value of T-statistic of 3.852> T-table (1.96) with the value of the path coefficient of 0.257, while the value of the indirect influence on the strategy of self leadership performance through mediator task commitment with path coefficient value of 0.053. These models can be used as a reference in improving the performance of midwives in other activities related to maternal and child health services.